Virtual precession-enabled phase error mitigation in high-precision hemispherical resonator gyroscopes - Li, Yida; Li, Heng; Gao, Feng; Shan, Yanhu; Wang, Xiaoyi; Cao, Huiliang; Xie, Huikai (Sensors and actuators. A. Physical., 2025)
This study proposes a novel virtual precession method to achieve real-time phase error identification in hemispherical resonator gyroscopes (HRGs) without turntables. By employing an Exponentially Weighted Recursive Least Squares (EWRLS) algorithm during self-precession, we dynamically extract phase-delay errors and structural errors caused by frequency splitting and damping asymmetry from angular velocity outputs and compensate Phase-Locked Loop (PLL). This approach eliminates coupling errors induced by quadrature control voltages and overcomes the dead-zone limitation in Whole-Angle mode. Experimental results demonstrate significant performance improvements: 34.05% reduction in bias instability (from 0.584°/h to 0.385°/h) and 85.81% suppression of scale factor nonlinearity (from 559.9 ppm to 79.4 ppm). The scheme enables autonomous compensation of HRG phase errors, enhancing long-term precision for inertial navigation applications. [Display omitted] •Virtual precession uses self-generated Coriolis forces for continuous error extraction at low angular rates.•Real-time phase error identification via Exponentially Weighted Recursive Least Squares (EWRLS) algorithm..•Closed-loop system enables real-time phase compensation by injecting EWRLS-identified errors.